2017
DOI: 10.1186/s13046-017-0656-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of EGR1 inhibits glioma proliferation by targeting CCND1 promoter

Abstract: BackgroundGliomas are the most common primary tumors in central nervous system. The prognosis of the patients with glioma is poor regardless of the development of therapeutic strategies. Its aggressive behavior mainly depends on the potent ability of proliferation. The transcription factor EGR1 (early growth response 1) is a member of a zinc finger transcription factor family which plays an essential role in cell growth and proliferation.MethodsEGR1 expression levels in 39 glioma tissues and 10 normal brain ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 37 publications
(44 reference statements)
1
28
0
Order By: Relevance
“…Previous research has demonstrated that ccnd1 serves an important role in promoting the development and progress of multiple types of human cancer, such as lung adenocarcinoma, glioma and renal cell cancer (46)(47)(48)(49). a previous study indicated that mir-374a inactivated the phosphoinositide 3-kinase (Pi3K)/aKT signaling axis through inhibiting ccnd1 and suppressing the progression of colon cancer (49).…”
Section: Ccnd1 Is Required For the Proliferation And Apoptosis Of Ht-mentioning
confidence: 99%
“…Previous research has demonstrated that ccnd1 serves an important role in promoting the development and progress of multiple types of human cancer, such as lung adenocarcinoma, glioma and renal cell cancer (46)(47)(48)(49). a previous study indicated that mir-374a inactivated the phosphoinositide 3-kinase (Pi3K)/aKT signaling axis through inhibiting ccnd1 and suppressing the progression of colon cancer (49).…”
Section: Ccnd1 Is Required For the Proliferation And Apoptosis Of Ht-mentioning
confidence: 99%
“…The abnormal expression of CCND1 promotes cell proliferation by regulating the cell cycle [30]. Previous researchers have demonstrated that CCND1, identi ed as a proto-oncogene, has an essential role in the development of many kinds of tumours, including lung adenocarcinoma, glioma and renal cell cancer [31][32][33]. In addition, some studies have shown that overexpression of CCND1 promotes tumour cell invasion and metastasis in breast cancer gastric cancer, leading to a poor prognosis [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…EGR1 (Early growth response 1), also known as NGFI-A, TIS8, ZIF268, or KROX-24, is a member of the EGR family of transcription factors (18). EGR1 exhibits a dual role of a tumor suppressor or a tumor-promoting factor in various carcinomas, by regulating cell cycle progression, apoptosis and malignant transformations (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%